2023
DOI: 10.15252/embj.2023113684
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA N6‐methyladenine incorporation via adenylate kinase 1 is suppressed by ADAL deaminase‐dependent 2′‐deoxynucleotide pool sanitation

Abstract: Intracellular decay of N6‐methyladenine (m6A)‐containing RNA potentially induces aberrant N6‐methyl‐2′‐adenine (6mdA) misincorporation into DNA. Biophysically, misincorporated 6mdA may destabilize the DNA duplex in a manner similar to bona fide methylated 6mdA DNA, thereby affecting DNA replication and transcription. Utilizing heavy stable isotope labeling and ultrasensitive UHPLC–MS/MS assay, we demonstrate that intracellular m6A‐RNA decay does not generate free 6mdA species, nor lead to any misincorporated D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Next, we injected m6ATP into zygotes and observed higher level of 6mA in the nuclei of 32-cell embryos compared with ATP-injected or ATPuntreated embryos (Fig 5C), consistent with studies done in mammalian cells, showing that m6A ribonucleotides can be converted to 6mA deoxyribonucleotides and incorporated into the genome through replication that is conserved in eukaryotes(Musheev et al, 2020;Liu et al, 2021). Finally, we found that knocking down the Hydractinia Adal1, homologs of which convert m6A ribonucleotides into inosine in plants and mammals(Chen et al, 2018b;Chen et al, 2023), also delayed EU incorporation beyond the 64-cell stage(Fig EV3E). Since Adal1 only acts on monomeric m6A, this experiment provides further evidence for the RNA degradation scenario over demethylation.Taken together, we conclude that m6A-marked RNAs are degraded into nucleotide form.…”
supporting
confidence: 88%
“…Next, we injected m6ATP into zygotes and observed higher level of 6mA in the nuclei of 32-cell embryos compared with ATP-injected or ATPuntreated embryos (Fig 5C), consistent with studies done in mammalian cells, showing that m6A ribonucleotides can be converted to 6mA deoxyribonucleotides and incorporated into the genome through replication that is conserved in eukaryotes(Musheev et al, 2020;Liu et al, 2021). Finally, we found that knocking down the Hydractinia Adal1, homologs of which convert m6A ribonucleotides into inosine in plants and mammals(Chen et al, 2018b;Chen et al, 2023), also delayed EU incorporation beyond the 64-cell stage(Fig EV3E). Since Adal1 only acts on monomeric m6A, this experiment provides further evidence for the RNA degradation scenario over demethylation.Taken together, we conclude that m6A-marked RNAs are degraded into nucleotide form.…”
supporting
confidence: 88%
“…Recently, murine ADAL was shown to catalyze deamination of DNA-derived 2-deoxy- N 6 -methyladenosine monophosphate (6mdAMP), which might potentially induce aberrant epigenetic markers via modified N 6 -methyadenosine di- or triphosphoate 56 . Using in vitro kinase assays, we showed that m 6 AMP, m 6,6 AMP, and i 6 AMP are barely converted to m 6 AD/TP, m 6,6 AD/TP, and i 6 AD/TP by AK (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies on m 6 A in recent years identified its intracellular role in RNA stability, translation, and microRNA biogenesis 14,53,54 , but the extracellular role of m 6 A has been elusive. The presence of m 6 AMP was reported in plants and mammals 31,55,56 , but it was simply considered an RNA degradation product. Since lysosome is one of the major RNA-degrading organelles, m 6 AMP will be quickly dephosphorylated to m 6 A by lysosomal phosphatase, and since m 6 AMP cannot be formed in ADK-deficient cells, it is likely that most intracellular m 6 AMP is generated by ADK-mediated phosphorylation of RNA catabolism-derived m 6 A.…”
Section: Adk-mediated Phosphorylation Of Modified Adenosinesmentioning
confidence: 99%